Academic Achievement and Psychologial Stress:Evidence From Turkey - Dede, Nazan; Özer, Aslıhan; Yıldırım, Osman (INT SCIENTIFIC CONFERENCE SGEM, 14, KILMENT OHRIDSKY BLVD, SOFIA, 1797, BULGARIA, 2008)
The topics of stress and academic achievement are becoming increasingly interesting to educational institutions and their members. The aim of this research is to examine the relationship between personality and academic achievement of the Students of Vocational school in a private University in Istanbul, Turkey. There is a significant correlation between the students' personalities which are depicted via adjective checklist and the students' stress level assessed by Abidin's Stress Scale. Adjective Check List (ACL) items consist of adjectives which are words and/or phrases used for description in daily life in Turkish Language. The original ACL was built by 230 items. By using factor analysis, 230 items were reduced to 100 items. The scale composed of 100 items is examined for psychometric properties and internal consistency. Abidin's Stress Scale and ACL are conducted in the same time to a sample of 425 Students of School of Vocational Studies. Stress level and personality correlates of ACL are of interest on two Counts. First, in using the ACL it is important to know what variables may be confounded with mood. Second, there exist correlations between personality and mood.
Keywords: Stress Scale; Academic Achievement; Adjective Checklist; Children; Stres Ölçeği; Akademik Başarı; Sıfat Listesi; Çocuklar